2008
DOI: 10.1007/s11250-008-9246-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct and maternal (co)variance components and genetic parameters for growth and reproductive traits in the Boran cattle in Kenya

Abstract: Direct and maternal (co)variance components and genetic parameters were estimated for growth and reproductive traits in the Kenya Boran cattle fitting univariate animal models. Data consisted of records on 4502 animals from 81 sires and 1010 dams collected between 1989 and 2004. The average number of progeny per sire was 56. Direct heritability estimates for growth traits were 0.34, 0.12, 0.19, 0.08 and 0.14 for birth weight (BW), weaning weight (WW), 12-month weight (12W), 18-month weight (18W) and 24-month w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 12 publications
2
18
2
1
Order By: Relevance
“…In a study on genetic and environmental causes of variation in body weight of Sahiwal cattle in Pakistan, Khan et al (1999) reported c 2 of 0.05 on calf weight under artificial milk feeding system. In a study on Boran cattle in Kenya, Wasike et al (2009) reported low maternal environmental variance at birth (c 2 =0.16); however, unlike in our study and those mentioned, maternal environmental effects played a great role accounting for a significant variation in pre-weaning growth. The relatively large phenotypic variances for pre-weaning growth performance in tropical cattle breeds under the cow-calf feeding system is a reflection of differences in individual dam's milk production and mothering ability (Orenge et al 2009;Wasike et al 2009), compared to artificial feeding systems where calves are subjected to relatively uniform feeding regimes (e.g.…”
Section: Resultscontrasting
confidence: 88%
“…In a study on genetic and environmental causes of variation in body weight of Sahiwal cattle in Pakistan, Khan et al (1999) reported c 2 of 0.05 on calf weight under artificial milk feeding system. In a study on Boran cattle in Kenya, Wasike et al (2009) reported low maternal environmental variance at birth (c 2 =0.16); however, unlike in our study and those mentioned, maternal environmental effects played a great role accounting for a significant variation in pre-weaning growth. The relatively large phenotypic variances for pre-weaning growth performance in tropical cattle breeds under the cow-calf feeding system is a reflection of differences in individual dam's milk production and mothering ability (Orenge et al 2009;Wasike et al 2009), compared to artificial feeding systems where calves are subjected to relatively uniform feeding regimes (e.g.…”
Section: Resultscontrasting
confidence: 88%
“…Wall et al (2003) reported a heritability estimate of 0.03 for calving interval between first and second calving of Australian and UK Holstein cows, and Gonzalez-Recio and Alenda (2005) reported an estimate of 0.04 on Spanish Holstein. Jagusiak and Zarnecki (2006) summarized estimates for CI from the literature to range from 0.00 (Wasike et al 2009) to 0.18 (Vergara et al 2009). Makgahlela et al (2007) reported a heritability estimate for South African Holstein cattle of 0.03, including calving intervals between different lactations as repeated measures.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of heritabilities (in bold on diagonal), genetic correlations (above the diagonal) and phenotypic correlations (below the diagonal) for AFC and productive traits in Iranian Holsteins (standard error of estimates are in bracketsAFC age at first calving,MY adjusted milk yield, MEMY mature equivalent milk yield, FY adjusted fat yield, FPER fat percentage, MEFY mature equivalent fat yield, PY protein yieldHereford beef cattle in Kenya, andMäntysaari et al (2002),Nilforooshan and Edriss (2004),Ilatsia et al (2007) andWasike et al (2009) found heritability estimates less than 0.10 for AFC. The heritability estimates for MY and FPER in this study were lower than the estimates reported by Ghavi Hossein-Zadeh and Ardalan (2011) in Iranian…”
mentioning
confidence: 99%